Born-corrections to weak lensing of the cosmic microwave background temperature and polarization anisotropies - Hagstotz, Steffen; Schäfer, Björn Malte; Merkel, Philipp M. (Monthly notices of the Royal Astronomical Society, 2015)
Many weak-lensing calculations make use of the Born approximation where the light ray is approximated by a straight path. We examine the effect of Born-corrections for lensing of the cosmic microwave background (CMB) in an analytical approach by taking perturbative corrections to the geodesic into account. The resulting extra power in the lensing potential spectrum is comparable to the power generated by non-linear structure formation and affects especially the polarization spectra, leading to relative changes of the order of 10−3 for the E-mode spectrum and several per cent on all scales to the B-mode spectrum. In contrast, there is only little change of spectra involving the CMB temperature. Additionally, the corrections excite one more degree of freedom resulting in a deflection component which cannot be described as a gradient of the lensing potential as it is related to image rotation in lens–lens coupling. We estimate the magnitude of this effect on the CMB spectra and find it to be negligible.